Research progress on biomarkers of early diagnosis and prognosis of cerebral small vessel disease - TANG Li⁃mo⁃ran; XU Yun (Chinese Journal of Contemporary Neurology and Neurosurgery, 2023)
Cerebral small vessel disease (CSVD) is an important risk factor for stroke, dementia and death，which seriously endangers the health and quality of life of the elderly. The onset of CSVD is insidious and there is a lack of early diagnosis methods and interventions, so the search for markers that can provide early warning of CSVD and prognosis assessment is very important for the prevention and treatment of the disease. This article reviews imaging and laboratory biomarkers for early diagnosis and prognosis of CSVD, in order to provide new ideas for the formulation of prevention, diagnosis and treatment strategies related to the disease.